SB IPOs and IPO Anomalies: An Empirical Analysis of the Small Firm Uniqueness Hypothesis - James C. Brau; C. Troy Carpenter (The Journal of Entrepreneurial Finance (JEF), 2013)
The purpose of this paper is to provide a direct test of the small-firm uniqueness hypothesis advanced by Ang (1991). We do this by using the 5B-IPO program of the SEC as our instrument to define a small firm. Having identified small firms, we test the three IPO anomalies to see if small firms differ from large firms along these dimensions. We find that 5B IPOs experience the three anomalies; however, they do so in disparate ways than mainline IPOs do. In sum, we provide support for the small firm uniqueness hypothesis.
Keywords: G24; G28; G38; M13; 650; IPO; Initial Public Offering; Anomalies; Small Firm Uniqueness; SB-2